Dhikr as an Adaptive Spiritual Strategy: Exploring the Healing Mechanism for Anxiety from The Islamic Perspective - Nurul Aisatul Masita; Cholil (Istisyarah: Jurnal Bimbingan Konseling Islam, 2025)
This study aims to explore in-depth individual experiences utilizing the practice of dhikr (remembrance of God) as a spiritual and holistic method for managing anxiety. Using a qualitative approach and a phenomenological design, this research focuses on the subjective meanings and cognitive, emotional, and physical changes experienced by subjects in response to regular dhikr practice. The study involved individuals aged 18 to 50 who experienced mild to moderate anxiety and had been practicing dhikr regularly for at least six months. Data were collected through in-depth interviews, participant observation, and reflective journals. Interpretive thematic data analysis revealed that dhikr functions as a spiritually integrated coping mechanism and results in a transformation of the experience of anxiety across three domains. Cognitively, dhikr is experienced as a "cognitive barrier" that consciously shifts the focus of attention from excessive anxious thoughts to an awareness of the Greatness of Allah Swt. Physiologically and emotionally, participants reported that the regular breathing pattern and rhythm of dhikr created a calming (relaxing) effect that connected them to a sense of thuma'ninah (deep inner calm), while simultaneously alleviating physical symptoms of anxiety (such as rapid heartbeat and muscle tension). Behaviorally and spiritually, dhikr was interpreted as a significant adaptive spiritual management tool. This practice strengthened spiritual fortitude and fostered self-confidence as participants felt divine "help" and support, making them feel more empowered in facing life's challenges.